The impact of the combination of baseline risk group and cytogenetic response on the survival of patients with chronic myeloid leukemia treated with interferon-α - Hasford, Joerg; Pfirrmann, M.; Shepherd, P.; Guilhot, J.; Hehlmann, Rüdiger; Mahon, F. X.; Kluin-Nelemans, H. C.; Ohnishi, K.; Steegmann, J. L.; Thaler, J. (Haematologica, the hematology journal, 2005)
Background and Objectives: This study was aimed at examining major cytogenetic response (MCR) as a valid predictor of the course of chronic myeloid leukemia (CML) and at assessing the survival of CML patients treated with interferon a (IFN) in dependence on the combination of MCR (yes or no) with the baseline risk group of the New CML score. MCR was defined as a reduction of Philadelphia chromosome-positive bone marrow cells to £ 35%. The New CML score discriminated three risk groups with significantly different survival probabilities. Design and Methods: Data from individual patients with a confirmed diagnosis of Philadelphia chromosome-positive CML treated with IFN were collected from 10 prospective studies in Europe and Japan. Stratified for baseline risk group, patients with a major cytogenetic response by 21 months after the start of therapy (n=171) were compared with patients achieving a minor response or less (n=487). Survival probabilities after the landmark at 21 months were compared by using the two-sided log-rank test. Results: MCR was a major predictor for low- and intermediate-risk patients (log-rank test, p £ 0.0001), but not for high-risk patients. Ten-year survival probabilities for the low- and intermediate-risk patients who had a MCR were 75% (95 CI: 65-86%) and 56% (95 CI: 37-75%), respectively. The corresponding probabilities for patients who did not achieve a MCR were 21% (95 CI: 6-35%) and 16% (95 CI: 6-25%). Interpretation and Conclusions: Cytogenetic response per se is not a valid surrogate marker, as it is dependent on the baseline prognostic profile. The combination of risk group and cytogenetic response does, however, provide useful clinical information. The survival data presented here can serve as a benchmark for the assessment of the long-term effectiveness of imatinib.
Gesehen am 12.05.2022
DOI funktioniert nicht